The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21037/atm-20-6448
|View full text |Cite|
|
Sign up to set email alerts
|

Aberrant amplitude low-frequency fluctuation (ALFF) and regional homogeneity (ReHo) in generalized anxiety disorder (GAD) and their roles in predicting treatment remission

Abstract: Background: Generalized anxiety disorder (GAD) is a common affective disorder characterized by comprehensive anxiety with dysregulation of brain activity which can be reflected by functional magnetic resonance imaging (f-MRI). We aimed to examine abnormal aberrant amplitude low-frequency fluctuation (ALFF) and regional homogeneity (ReHo) in GAD and evaluate their ability to predict treatment remission. Methods: Using resting-state fMRI (Rs-fMRI), we examined ALFF and ReHo in 30 GAD patients and 30 healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…The insula/Rolandic operculum are implicated in interoceptive, salience and emotion processing (42). Restingstate fMRI and lesion studies suggested that deficits in Rolandic operculum are associated with GAD and high anxiety and perceived stress which characterizes GAD (43,44). The left IFG has been consistently reported in previous meta-analyses examining brain structural markers of both, GAD (22) and mixed AD (27,28).…”
Section: Discussionmentioning
confidence: 86%
“…The insula/Rolandic operculum are implicated in interoceptive, salience and emotion processing (42). Restingstate fMRI and lesion studies suggested that deficits in Rolandic operculum are associated with GAD and high anxiety and perceived stress which characterizes GAD (43,44). The left IFG has been consistently reported in previous meta-analyses examining brain structural markers of both, GAD (22) and mixed AD (27,28).…”
Section: Discussionmentioning
confidence: 86%
“…Previous study has proposed that the postcentral gyrus plays an important role in emotional regulation [70]. The alteration of amplitude of low-frequency fluctuation (ALFF) and ReHo values in the postcentral gyrus could be used as a biomarker for generalized anxiety disorder [71]. Besides, Qi et al [72] found increased gray matter volume in depression patients with anxiety disorder compared with healthy controls in the postcentral gyrus.…”
Section: 9786mentioning
confidence: 99%
“…The discrepant results might be attributed to patient heterogeneity, migraine phases and study methodology. Additionally, the regional neural activity of the MFG was reported to be effective in predicting the treatment efficacy of pain and anxiety through drug therapy [39] and transcranial magnetic stimulation [40].…”
Section: M-oa Vs Hcsmentioning
confidence: 99%